Implementasi Program Skrining Kesehatan dan Edukasi Pola Hidup Sehat dalam Upaya Pencegahan Penyakit Tidak Menular - Muhammad Diva Pratama; Idhfi Marpatmawati; Meti Kusmiati; Anisa Anisa; Jenisa Nadhia Fadhillah; Natasya Budi Aulia; Gina Yuniartina; Yulistiani Yulistiani; Nenden Maida Ayuningsih; Gianova Akhsan Robbany; Ernawati Ningsih (LPMP Imperium, 2026)
Non-Communicable Diseases (NCDs), including hypertension and diabetes mellitus (DM), are increasingly prevalent health concerns with the potential to cause serious complications, such as visual impairment. Insufficient public awareness regarding early detection of risk factors remains a primary contributor to delayed treatment. The Community Service Program was designed to enhance public knowledge and awareness through educational initiatives and early detection of NCD risk factors and eye health issues. The program was conducted using a participatory, in-person approach that incorporated health education and basic health screenings. The target population comprised residents of RT 03/RW 11 Kampung Sukasukur, with the involvement of local health cadres. Success indicators included community participation rates, the effective execution of screening activities, and the identification of health risk factors. The program achieved active community engagement. Health screenings identified a high prevalence of hypertension (70%), as well as several individuals with elevated uric acid and cholesterol levels. Additionally, two cases of cataracts and multiple instances of eye complaints, such as red eyes, were detected. The program positively influenced public understanding of healthy lifestyles and the importance of early disease detection, while also generating health data for use by health cadres in subsequent interventions.